Epilepsy - Brodie, Martin J; Schachter, Steven C; Kwan, Patrick Kwok Leung (Health Press, 2005)
This new third edition is an outstanding contribution to the armoury of the family physician and, indeed the training neurologist. Not only is this text invaluable as a succinct and practical aid to diagnosis and subsequent treatment of a wide range of seizure disorders, it is also an excellent teaching tool. This book includes a new section on the principles of antiepileptic drug (AED) selection with the very latest information on available drugs. A new chapter covers the psychiatric morbidities and social aspects of the disorder. The updated chapter on non-pharmacological management includes the latest information on the ketogenic diet and alternative medicine. It explains our current understanding of the genetics that underpin the mechanisms of neuronal excitation and inhibition. It includes new information specific to women with epilepsy.
Fast facts
Keywords: status epilepticus; prognóza; Disease Management; Prognosis; kvalita života; Epilepsy; Anticonvulsants; epilepsie; Status Epilepticus; Quality of Life; antikonvulziva; management nemoci; neurologie